HORMONAL STATUS AS A DETERMINANT OF FILLER CHOICE IN FERTILE-AGE WOMEN OF THE CENTRAL ASIAN POPULATION: A COMPARATIVE ANALYSIS - M.A. Khalmatova,; I. R. Khasanov,; M. Sh. Khariyeva, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Relevance: Aesthetic  facial  correction  using  dermal  fillers  requires consideration of ethnic skin characteristics and the influence of the patient’s hormonal background [1, 2]. The hormonal profile of women of fertile age directly affects the structural and functional properties of the skin, which must be taken into account when planning injection techniques [9, 10]. Objective: To develop an algorithm for selecting dermal fillers for women of fertile age in the Central Asian population, taking into account hormonal characteristics and skin structure specifics. Materials and Methods: A systematic analysis of literature data was performed, including studies on Asian skin characteristics,  hormonal profiles, and comparative effectiveness of fillers.